Pengaruh Pernikahan Dini terhadap Pengelolaan Keuangan Rumah Tangga pada Pasangan Muda di Kecamatan Ampana Kota Kabupaten Tojo Una-Una - Samangka, Nurhayati H; Karim, Sitti Aminah Hamzah (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to examine the influence of early marriage on household financial management in Ampana Kota District, Tojo Una-Una Regency. The research uses a quantitative method with a survey approach to statistically measure the relationship between variables. Data were collected through questionnaires. The population in this study consists of married couples who entered into early marriages between 2022 and 2024 and reside in Ampana Kota District. The sampling technique used was total sampling, involving 55 couples who married under the age of 19 and whose marriages have lasted less than three years within the 2022–2024 period. The results of data analysis show that early marriage significantly influences the ability of young couples to manage household finances. These findings indicate that early marriage not only affects social and psychological aspects but also has a direct impact on the economic condition of the family, particularly in terms of financial planning, management, and the wise use of household resources